Pengaruh Opini Audit dan Temuan Audit Badan Pemeriksa Keuangan terhadap Kinerja Keuangan Pemerintah Daerah (Studi Kasus pada Pemerintah Kabupaten dan Kota di Provinsi Jawa Barat 2019-2023) - Aprilia, Dilla; Hendaris, Raden Budi (Universitas Batanghari Jambi, 2025)
This study aims to analyze the influence of audit opinions and findings issued by the Supreme Audit Agency on the financial performance of 27 district and city governments in West Java Province during the period 2019-2023. The data used in this study are secondary data obtained from the official website of the West Java Provincial Audit Agency and the Central Statistics Agency (CSA) of West Java Province. The analysis method used is multiple linear regression. The results of the analysis indicate that simultaneously, audit opinions and findings have a significant influence on the financial performance of local governments. However, partially, audit opinions have a positive effect, while audit findings have a negative and significant effect on the financial performance of district and city governments in West Java Province 2019-2023.